PENGARUH RASIOLIKUIDITAS, RASIO PRODUKTIVITAS, RASIO PROFITABILITAS, DAN RASIO SOLVABILITAS TERHADAP PERINGKAT SUKUK - Endah Winanti, Siti Nurlaela, Kartika Hendra Titisari (ITB AAS INDONESIA, 2017)
This research aims to find out if there is liquidity ratio, the ratio of influence productivity, pofitabilityratio, and the ratio of solvability against ranking sukuk made on companies listed at the IDX in 2011-2015. Type of this research is quantitative research. The sample used in this study was 14 companies that issue the sukuk and listed on the Indonesia stock exchange in 2011-2015, with purposive sampling method sampling. Methods of data analysis used in this study was multiple linear regression test. Based on the results of the research that has been done, then it can be taken a few conclusions, namely: Liquidity ratio does not affect the ranking of sukuk. Productivity ratio to rank sukuk, so the magnitude of this productivity ratio illustrates the effectiveness of the management of the company and so did to rank sukuk. Profitability ratio did not affect the ranking of sukuk. Solvability ratio effect on the ranking of sukuk.Key Word : Sukuk, Liquidity, Productivity, Solvability.